Development and Optimization of SARS-CoV-2-Specific Primers for Accurate Diagnosis: A Case Study in West Sumatra - Indonesia - Aulia, Ony Nattasha; Putri, Dwi Hilda; Faizal, Irvan (Althea Medical Journal, 2024)
Background: In 2022, new cases of Covid-19 emerged, including the Omicron variant which is classified as a variant of concern (VOC). West Sumatra is one of the top ten provinces with the highest number of cases in Indonesia. This study aimed to design specific primers and optimize the PCR method that can be used for accurate detection, specifically for SARS-CoV-2 circulating in West Sumatra.Methods: This study used an in silico approach, using whole genome sequencing (WGS) data available at the global initiative on sharing avian influenza data (GISAID), and employing the Geneious Prime application which confirmed samples collected from Padang, West Sumatra, and from Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek) serving as comparative sample tests. Technology development was supported by bioinformatics testing, laboratory testing, and validation methods, involving gene mining, sequence alignment, and primer design. Laboratory tests and validation included viral genomes extraction and cDNA synthesis, polymerase chain reaction (PCR) testing, and results analysis. Results: Three sets of optimal primer candidates amplified the coveted target gene was discovered, specifically, the S gene of the receptor binding domain (RBD) region.Conclusions: The primers designed through a consensus between the complete genome of the SARS-CoV-2 isolate Wuhan-Hu-1 and the WGS of the Omicron variant in Padang, West Sumatra, have successfully detected the SARS-CoV-2 virus variant in the region. The most effective temperature optimization results were achieved by testing three primer products on samples from Padang and Jabodetabek. It has significance as a valuable diagnostic tool in the primer form.